2005
DOI: 10.1007/s11046-004-6987-7
|View full text |Cite
|
Sign up to set email alerts
|

The use of new probes and stains for improved assessment of cell viability and extracellular polymeric substances in Candida albicans biofilms

Abstract: Phenotypic and genotypic cell differentiation is considered an important feature that confers enhanced antifungal resistance in candidal biofilms. Particular emphasis has been placed in this context on the viability of biofilm subpopulations, and their heterogeneity with regard to the production of extracellular polymeric substances (EPS). We therefore assessed the utility of two different labeled lectins Erythrina cristagalli (ECA) and Canavalia ensiformis (ConA), for EPS visualization. To evaluate the viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 25 publications
3
102
0
9
Order By: Relevance
“…1). We (and others) have previously shown that the XTT-reduction assay shows excellent correlation between cellular density and metabolic activity, thus providing a semiquantitative measurement of biofilm formation [22][23][24][25][26] . This colorimetric assay is non-invasive and non-destructive, requiring minimal postprocessing of samples as compared to other alternative methods (such as viable cell counts) and has the additional advantage that, in contrast to other methods such as crystal violet staining and dry mass measurements, it correlates with cell viability which is particularly useful for measuring the effects of drugs on biofilm cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). We (and others) have previously shown that the XTT-reduction assay shows excellent correlation between cellular density and metabolic activity, thus providing a semiquantitative measurement of biofilm formation [22][23][24][25][26] . This colorimetric assay is non-invasive and non-destructive, requiring minimal postprocessing of samples as compared to other alternative methods (such as viable cell counts) and has the additional advantage that, in contrast to other methods such as crystal violet staining and dry mass measurements, it correlates with cell viability which is particularly useful for measuring the effects of drugs on biofilm cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, alterations in the metabolic states during the different phases of biofilm formation may lead to fluctuations in the ability of cells within the biofilms to metabolize this dye 23,27 . Some more recent articles indicate that the use of other vital stains (SYTO9, propidium iodide), fluorogenic assays or bioluminescence may represent alternatives and have some practical advantages over the use of XTT 23,24,28 . This 96 well microtiter plate model for biofilm formation was originally developed for C. albicans and other Candida spp.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of xanthochymol or garcinol, large propidium iodide-positive areas (red staining) were evident, characteristic of inviable cells with leaky membranes ( Fig. 2A and B) (28). Close examination of treated biofilms showed that both compounds were effective at killing hyphae present in the mature biofilm, whereas the yeast form cells were Syto-9 positive (green), indicating they were viable.…”
Section: Resultsmentioning
confidence: 95%
“…Silva et al (13) claim that it is expected that concentrations higher than the MIC could interfere on biofilms at metabolic levels, but it is not fully understood whether antifungal agents at concentrations higher than MIC could actually affect the biofilm architecture. According to Jin et al (14), many coloring substances may be used to allow quantification of microbial biofilms, such as the FUN-1 dye, widely used in the investigation of antifungal resistance and cell viability of C. biofilms. However, these authors pointed out that the FUN-1 could lead to overestimation of living cells, especially when cell density is high.…”
Section: Discussionmentioning
confidence: 99%